Large Volume Fluid Resuscitation for Severe Acute Pancreatitis is Associated With Reduced Mortality: A Multicenter Retrospective Study. Issue 5 (May 2019) - Yamashita, Takahiro; Horibe, Masayasu; Sanui, Masamitsu; Sasaki, Mitsuhito; Sawano, Hirotaka; Goto, Takashi; Ikeura, Tsukasa; Hamada, Tsuyoshi; Oda, Takuya; Yasuda, Hideto; Ogura, Yuki; Miyazaki, Dai; et al.
Abstract : Background and Aims: Although fluid resuscitation is critical in acute pancreatitis, the optimal fluid volume is unknown. The aim of this study is to evaluate the association between the volume of fluid administered and clinical outcomes in patients with severe acute pancreatitis (SAP). Methods: We conducted a multicenter retrospective study at 44 institutions in Japan. Inclusion criteria were age 18 years or older, and diagnosed with SAP from 2009 to 2013. Patients were stratified into 2 groups: administered fluid volume <6000 and ≥6000 mL in the first 24 hours. We evaluated the association between the 2 groups and clinical outcomes using multivariable logistic regression analysis. The primary outcome was in-hospital mortality. Secondary outcomes included the incidence of pancreatic infection and the need for surgical intervention. Results: We analyzed 1097 patients, and the mean fluid volume administered was 5618±3018 mL (mean±SD), with 708 and 389 patients stratified into the fluid <6000 mL and fluid ≥6000 mL groups, respectively. Overall in-hospital mortality was 12.3%. The fluid ≥6000 mL group had significantly higher mortality than the fluid <6000 mL group (univariable analysis, 15.9% vs. 10.3%; P <0.05). In multivariable logistic regression analysis, administration of ≥6000 mL of fluid within the first 24 hours was significantly associated with reduced mortality (odds ratio, 0.58; P <0.05). No significant association was found between the administered fluid volume and pancreatic infection, or between the volume administered and the need for surgical intervention. Conclusions: In patients with SAP, administration of a large fluid volume within the first 24 hours is associated with decreased mortality.